The potential of the bullion business in accelerating financial inclusion: A theoretical review of Pegadaian’s strategic role - Nurkholifatul Maula; Najhah Barnamij (Institute for Advanced Social, Science, and Sustainable Future, 2026)
Background: Formalizing bullion banking in Indonesia represents a strategic financial evolution catalyzed by the Law on the Development and Strengthening of the Financial Sector (P2SK) and OJK Regulation No. 17 of 2024. This study aims to construct a macroeconomic value proposition for the bullion business scheme, identifying it as a critical driver for strengthening the